Splenic Circumference at Midpregnancy as a Predictor of Hemoglobin Bart's Disease among Fetuses at Risk - Srisupundit K. (2014)
Objective: To determine the accuracy of splenic circumference in predicting hemoglobin (Hb) Bart's disease among fetuses at risk at midpregnancy. Materials and Methods: Women with singleton pregnancies with a fetal risk of Hb Bart's disease were enrolled in the study at 18-22 weeks of gestation. All underwent splenic circumference measurement before cordocentesis for fetal blood analysis. The final diagnosis used as a gold standard was based on fetal Hb typing using high-performance liquid chromatography. Results: Among all the pregnancies, the prevalence of Hb Bart's disease was 26.1% (87/334 fetuses). Twenty-four fetuses (27.6%) had some degree of hydropic changes. Notably, of these 24, 22 showed splenomegaly as well. When hydropic fetuses were excluded, the sensitivity, specificity, positive predictive value and negative predictive value of splenic circumference in identifying affected fetuses were 68.3, 83.0, 50.6 and 91.1%, respectively. Conclusion: Splenic circumference measurement at midpregnancy may be helpful in distinguishing affected fetuses from those unaffected. Among couples at risk with normal splenic size, the risk of having an affected child is much lower, whereas the enlarged spleen places the pregnancy at a higher risk. This information may help couples decide on invasive diagnosis or a noninvasive approach. Copyright © 2011 S. Karger AG, Basel.